PENGARUH GOOD CORPORATE GOVERNANCE, CORPORATE SOCIAL RESPONSIBILITY, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Study Empiris pada Perusahaan yang Terdaftar di Bursa Efek Indonesia Periode 2017-2020) - Khilmia Ramadhani; Moh. Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2021)
This study aims to analyze the effect of good corporate governance, corporate social responsibility, and profitability on firm value as measured by using the corporate governance perception index (CGPI), corporate social responsibility index (CSRI), Return on assets (ROA) and price to book value (PBV). The research population is manufacturing companies listed on the Indonesian stock exchange during the 2017-2020 period. The samples is 42 companies. The data analysis technique used is Multiple Linear Regression. The results of this study indicate that Good Corporate Governance has no significant effect on firm value. Corporate Social Responsibility has a significant negative effect on firm value, and profitability has a positive and significant effect on firm value. Simultaneously all independent variables affect firm value.Keywords: Good Corporate Governance, Corporate Social Responsibility, Profitability, Firm Value